Deciphering in silico the Role of Mutated NaV1.1 Sodium Channels in Enhancing Trigeminal Nociception in Familial Hemiplegic Migraine Type 3 - Suleimanova, Alina; Talanov, Max; van den Maagdenberg, Arn M. J. M.; Giniatullin, Rashid (Frontiers in Cellular Neuroscience, 2021)
Familial hemiplegic migraine type 3 (FHM3) is caused by gain-of-function mutations in the SCN1A gene that encodes the α1 subunit of voltage-gated NaV1.1 sodium channels. The high level of expression of NaV1.1 channels in peripheral trigeminal neurons may lead to abnormal peripheral nociceptive signaling thus contributing to migraine pain. NaV1.1 dysfunction is relevant also for other neurological disorders, foremost epilepsy and stroke that are comorbid with migraine. Here we used computer modelling to test the functional role of FHM3 mutated NaV1.1 channels in mechanisms of trigeminal pain. The activation of Aδ-fibers was studied for two algogens, ATP and 5-HT, operating through P2X3 and 5-HT3 receptors, respectively, at trigeminal nerve terminals. In WT Aδ-fibers of meningeal afferents, NaV1.1 channels efficiently participate in spike generation induced by ATP and 5-HT supported NaV 1.6 channels. Of the various FHM3 mutations tested, the L263V missense mutation, with a longer activation state and lower activation voltage, resulted in the most pronounced spiking activity. In contrast, mutations that result in a loss of NaV1.1 function largely reduced firing of trigeminal nerve fibers. Combined activation of P2X3 and 5-HT3 receptors and branching of nerve fibers resulted in very prolonged and high-frequency spiking activity in the mutants compared to WT. We identified, in silico, key determinants of long-lasting nociceptive activity in FHM3-mutated Aδ fibers that naturally express P2X3 and 5-HT3 receptors and suggest mutant-specific correction options. Trigeminal nerve firing was significantly higher for FHM3 mutations, compared to WT, suggesting that pronounced nociceptive signaling may contribute to migraine pain.